The Importance of Alliance between Hematologists and Dentists: A Retrospective Study on the Development of Bisphosphonates Osteonecrosis of the Jaws (Bronj) in Multiple Myeloma Patients - Christian Bacci; Alessia Cerrato; Virginia Dotto; Renato Zambello; Gregorio Barilà; Albana Liço; Gianpietro Semenzato; Edoardo Stellini; Gastone Zanette (MDPI AG, 2021)
(1) Background: Multiple myeloma is a rare cancer that primarily affects the bone marrow. Osteoclasts are responsible for increased bone resorption and, therefore, bone destruction. Bisphosphonates are a class of drugs that can slow down bone resorption by reducing the number and action of osteoclasts. Intravenous injections of bisphosphonates (generally Zoledronic Acid) are administered to patients affected by Multiple Myeloma, but BRONJ is described as a serious side effect. This 5-year retrospective study aims to evaluate the efficacy of appropriate dental treatment protocols prior to initiating bisphosphonate therapy to prevent the development of BRONJ. (2) Methods: A total of 99 patients with symptomatic multiple myeloma were involved in this study (41-90 years, mean age 65 years, standard deviation 5 years). The data relating to the visits were tracked using a specific server and consulting the clinical reports. The AAOMS (American Association of Oral and Maxillofacial Surgeons) position was applied for both diagnosis and treatment. A total of 79 patients were examined before the administration of bisphosphonates (group A) and 20 after (group B). (3) Results: The entire sample required dental treatment: 23.2% underwent restorative therapy, 8% endodontic treatments, 44.4% tooth extractions. Periodontal disease was present in 41.4% of the patients. No osteonecrosis was observed in the first group, whereas BRONJ was found in five patients of the second one (25%) and two patients (10%) showed osteosclerotic areas under investigation [OR 0.026 (CI 0.0027 to 0.2454)]. (4) Conclusions: In the literature, there are no precise data about the prevalence of BRONJ. Despite the limitation of the present study, we point out that dental treatment before the treatment with intravenous bisphosphonates can help in reducing the incidence of BRONJ and good dental status is necessary for BRONJ prevention.